2018
DOI: 10.1101/483826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic Biology - Mapping the Patent Landscape

Abstract: This article presents the global patent landscape for synthetic biology as a new and emerging area of science and technology. The aim of the article is to provide an overview of the emergence of synthetic biology in the patent system and to contribute to future research by providing a high quality tagged core dataset with 7,424 first filings and 71,887 family members. This dataset is intended to assist with evidence based exploration of synthetic biology in the patent system and with advancing methods for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…What sets the case of synthetic biology and gene drives apart from the debate on agricultural biotechnology during the 1990s is that, at least for the time being, a significant amount of research and development is being carried out in the public and philanthropic sectors rather than in the for-profit private sector. Patent activity remains relatively limited (Oldham and Hall, 2018). In addition, as synthetic biology technologies become less expensive and more widely accessible, several small-scale, publicly accessible community laboratories, do-it-yourself and open science collaborations are emerging that may lead to a democratization of science (Laird and Wynberg, 2018).…”
Section: Synthetic Biology and Gene Drivesmentioning
confidence: 99%
“…What sets the case of synthetic biology and gene drives apart from the debate on agricultural biotechnology during the 1990s is that, at least for the time being, a significant amount of research and development is being carried out in the public and philanthropic sectors rather than in the for-profit private sector. Patent activity remains relatively limited (Oldham and Hall, 2018). In addition, as synthetic biology technologies become less expensive and more widely accessible, several small-scale, publicly accessible community laboratories, do-it-yourself and open science collaborations are emerging that may lead to a democratization of science (Laird and Wynberg, 2018).…”
Section: Synthetic Biology and Gene Drivesmentioning
confidence: 99%
“…Several studies show that across the world, the numbers of patents on plants and plant genetic material (King & Schimmelpfennig, 2005;Louwaars et al, 2009;WIPO, 2019), as well as of patents on NBTs (Oldham & Hall, 2018), are rapidly growing. Brinegar et al (2017) showed that the number of patent applications filed in gene-editing technologies increased 15-fold since 2005, while Martin-Laffon et al ( 2019) showed the steep rise in the number of patents to be related to the application of the CRISPR gene-editing technology in different parts of the world, with China and the United States being far ahead.…”
Section: Trends In Patenting Of Nbts and Gene-edited Plantsmentioning
confidence: 99%
“…Brinegar et al (2017) showed that the number of patent applications filed in gene-editing technologies increased 15-fold since 2005, while Martin-Laffon et al ( 2019) showed the steep rise in the number of patents to be related to the application of the CRISPR gene-editing technology in different parts of the world, with China and the United States being far ahead. Oldham and Hall (2018) showed that the number of countries in which patent applicants seek protection for their inventions in the field of synthetic biology is growing as well.…”
Section: Trends In Patenting Of Nbts and Gene-edited Plantsmentioning
confidence: 99%
See 2 more Smart Citations